Becoming a missional church : the case of Evangelical Lutheran Church in Southern Africa (ELCSA) - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2013)
Dissertation (MA(Theol))--University of Pretoria, 2012.